Wernicke’s Encephalopathy Due to Hyperemesis Graviderum : A Rare Presentation (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Wernicke’s encephalopathy is a common and preventable acute neurological symptom due to deficiency of thiamine. Alcoholism also causes Thiamine deficiency. It can occur in non-alcoholic conditions such as prolonged starvation, hyperemesis graviderum, bariatric surgery, HIV, AIDS. The characteristics clinical triad of disease is ophthalmoplagia,ataxia & global confusion. Here a patient was studied who was diagnosed on M.R.I as Wernicke’s encephalopathy.Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 54-56